Estimation and differentiation movements of a terrestrial surface in Antarctic Region - Tretyak, K. R.; Golybinka, Y. I. (Ukrainian Antarctic Journal, 2006)
By results of repeated supervision in Antarctic Region the estimation and differentiation movements of a terrestrial surface at global (Antarctic plate), regional (Antarctic peninsula) and local (Argentina islands) levels is executed.